The credibility analysis of the microteaching assessment instrument based on the responses of biology education students using the Rasch model - Bowo Sugiharto; Murni Ramli (JURNAL BIOEDUKATIKA, 2020)
The credibility analysis of the microteaching assessment instrument based on the responses of biology education students using the Rasch model. This study aims to reveal the credibility of the microteaching (MT) assessment instrument by analyzing the responses of biology education students using the Rasch model. The biology education students as participants played roles as assessors and practitioners of MT. The instrument used was the Instrument of Assessing the Learning Implementation (IPPP) in Book 4 of the 2013 In-Service Teacher Training Program (PLPG) Guidelines issued by the Human Resources Development Agency (BPSDM) of the Ministry of Education and Culture. The data obtained were analyzed by multirater analysis of Many-Facet Rasch Measurement (MFRM) version 3.83.2. Based on the results and discussion, this study concluded that the MT assessment instrument in biology education using IPPP was quite credible, which was revealed from the following three points: 1) The responses of students practicing MT are based on the results of peer ratings on a logit scale ranging from -0.82 to 0.80, which means that students practicing were quite diverse and can be distinguished by the instruments; 2) Student responses as assessor to the MT assessment instrument in logit scale units ranged -1.99 to 0.94 which means that as an assessor, student were able to assess diversely. The student as assessor was also able to understand the different rating scales used; and 3) The results of the calibration of the instruments showed that 24 instrument items can provide accurate information about the performance of the practitioner with logit values ranged from a scale of -0.72 to 0.66.